2016
DOI: 10.3892/ol.2016.4669
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic evaluation of sorafenib for hepatocellular carcinoma using contrast-enhanced ultrasonography: Preliminary result

Abstract: Abstract. The present study aimed to determine the usefulness of contrast-enhanced ultrasonography (CEUS) with Sonazoid in evaluating the therapeutic response to sorafenib for hepatocellular carcinoma (HCC). In total, 26 patients with advanced HCC who received sorafenib and were followed up by CEUS were enrolled in the present study. CEUS was performed prior to and within 2-4 weeks of treatment, and the images of the target lesion in the post-vascular phase with a re-injection method were analyzed. The presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Interestingly, patients who received sorafenib initially, then SIRT upon progression responded similarly as patients who never received sorafenib, indicating that sorafenib treatment is still feasible after SIRT. This is in line with the mode of action of sorafenib which appears to have mainly normalization effects on the architecture of tumor vessels rather than inhibiting vascularization perse [14]. Further, patients who received sorafenib having progressed after SIRT had been performed had a markedly increased survival over the other cohorts.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, patients who received sorafenib initially, then SIRT upon progression responded similarly as patients who never received sorafenib, indicating that sorafenib treatment is still feasible after SIRT. This is in line with the mode of action of sorafenib which appears to have mainly normalization effects on the architecture of tumor vessels rather than inhibiting vascularization perse [14]. Further, patients who received sorafenib having progressed after SIRT had been performed had a markedly increased survival over the other cohorts.…”
Section: Discussionsupporting
confidence: 69%
“…However, the benefits of Sonazoid CEUS were recently reported, including its usefulness for evaluation and early detection of major adverse events [173]. It has been reported that analysis of the TIC and arrival time parametric imaging were useful for evaluating early response to sorafenib for advanced HCC [173,[178][179][180][181][182]. Although Sonazoid enables the evaluation of vascularity during systemic therapy that cannot be detected by CECT or contrast-enhanced MRI, Sonazoid may only be useful to evaluate treatment response if the number of HCCs is less than two or three.…”
Section: Monitoring Treatment Response For Systemic Therapymentioning
confidence: 99%
“…In addition to the diagnostic value, CEUS is playing important roles in the assessment of therapeutic responses of HCC. It is reported that CEUS could evaluate the intra-tumor vascularization of HCC after antiangiogenic treatment [21], ablative therapies [22], and transarterial chemoembolization [23].…”
Section: Discussionmentioning
confidence: 99%